(untitled) (Bioscience Journal, 2020)
This study investigated the effectiveness of the urine sample collection method in predicting the volume urinary and synthesis of microbial nitrogen. Eight fistulated steers were used with accessible rumens and kept in individual stalls. Their diets consisted of corn silage; corn silage + concentrate; corn silage + concentrate with addition of lipids in the form of soybean oil; and corn silage + concentrate with addition of lipids in the form of soybean grains. Estimates of microbial protein synthesis were obtained based on the urinary excretion of purine derivatives. There was no effect of diets on daily creatinine excretion (P>0.05). There were differences (P<0.05) between the urinary volume and microbial synthesis values determined by the total urine collection and those estimated from the urine spot samples and equations proposed by different authors. The estimation of microbial synthesis based on the urine excretion of purine derivatives should be performed from the total collection of the urine for a period of 24 hours.